Comparative evaluation of the aphicidal activity from Ziziphus spina-christi leaf and stem bark extracts against Aphis fabae Scopoli - Guezzoun, Nassima; Khezzani, Bachir; Selmane, Mehdi; Zemmouli, Naoual (Future Science, 2025)
Recently, using plants as a renewable source of bioactive mole-cules has aroused worldwide interest in the search for environ-mentally friendly alternatives that are less toxic and less costly than chemical pesticides. The black aphid Aphis fabae Scopoli (Homoptera: Aphididae) is a major insect pest that considerably compromises the quality and productivity of bean crops. This study aimed to compare the aphicidal activity of extracts derived from the medicinal plant Ziziphus spina-christi (L.) (Rhamnaceae) against Aphis fabae to determine and select the most potent ex-tracts in terms of toxicity. We treated aphid larvae and adults with various extracts (of hexane, dichloromethane, methane and water) from the leaves and stem bark of the plant using laborato-ry contact toxicity methods. The toxicity of the extracts was as-sessed based on the percentage of residual population (PR%) in aphid larvae and adults. Our results indicate that the methanolic extracts of Z. spina-christi leaves and bark had the lowest residual population percentages (RP less than 30%) compared with those recorded for the other extracts. The methanol extracts were more toxic to Aphis fabae larvae than adults. We conclude that methanol extracts of Z. spina-christi, particularly the stem bark methanol extract, can be considered an effective botanical aphi-cide harmless to the health and environment and therefore can be used to combat aphids as an alternative to chemical insecti-cides.